Sierra Leone series: Freetown Teachers College and its multimodal approach to teacher professional development - McBurnie, Chris; Moriba, Sambo; Brainard, Prince (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector. In week two, we connected with Dr Samba Moriba and Prince Brainard from Freetown Teachers…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4584801 2339240:F47KL5P7 2339240:VJ2SHXTR 2405685:DJHAECID 2405685:JV4FPSJW
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodoETH; dode_eth-src-eth

Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
ZenodoArchiveID: 4746391 previousDOI: 10.5281/zenodo.4746391 previousDOI: 10.5281/zenodo.4664510 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4664510 10.5281/zenodo.4746391 2339240:CJNJNHNU 2405685:RTQ64R3P 2405685:TD3Y79BH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH